1992
DOI: 10.1073/pnas.89.15.6911
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of Glu-953 of the alpha chain of Na+,K(+)-ATPase associated with inactivation of cation occlusion.

Abstract: We have investigated the role, number, and identity of glutamate (or aspartate) residues involved in cation occlusion on Na+,K+-ATPase, using the carboxyl reagent N,N'-dicyclohexylcarbodiimide (DCCD). Extensive use is made of selectively trypsinized Na+,K+-ATPase--the so-called "19-kDa membranes"-containing a 19-kDa COOHterminal, smaller (8-11 kDa) membrane-embedded fragments of the a chain, and a largely intact ( measured by examination of labeling of 19-kDa peptide purified from "19-kDa membranes" or of a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
1
1

Year Published

1993
1993
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 29 publications
1
58
1
1
Order By: Relevance
“…While the present study shows that Na' and K' binding take place in the Glu329+Gln variant, it does not exclude that the residue modified with DCCD in [5] was G~u~*~. The bulky DCCD molecule might have disturbed ion binding and occlusion, even if the modified residue were located at the periphery of the cation-binding pocket without being an essential component.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…While the present study shows that Na' and K' binding take place in the Glu329+Gln variant, it does not exclude that the residue modified with DCCD in [5] was G~u~*~. The bulky DCCD molecule might have disturbed ion binding and occlusion, even if the modified residue were located at the periphery of the cation-binding pocket without being an essential component.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, it was found that each mol of asubunit bound 2 mol of DCCD. One labeled residue was located in a cyanogen bromide fragment of apparent M, 4 kDa, and [r4C]DCCD incorporation was found to be associated almost exclusively with G1u953 [5]. The role of G1u953 was, however, tested in a recent mutagenesis study, and it was shown that cation stimulation of Na',K+-ATPase activity was unaffected by single amino acid substitutions of G1u953 [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations